Emotional problems in young children during the SARS-CoV-2-pandemic and child attachment - Zwönitzer, Annabel; Rost, Katharina; Fegert, Jörg M.; Ziegenhain, Ute; Köhler-Dauner, Franziska (Frontiers in Pediatrics, 2023)
Background Restrictions imposed by national governments during SARS-CoV-2-pandemic have impacted the mental health of children around the world. Studies have already proven the importance of secure attachment acting as a protective factor in child development. Therefore, children with a secure attachment have a higher chance of developing and using appropriate coping mechanisms. Objective The goal of this study was to explore the possible connection between the pandemic, as well as child attachment, and young children’s emotional health. The general hypothesis assumes a lower rate of emotional problems among children with secure attachment and a higher rate of emotional problems among children with insecure-disorganized attachment, as well as an increase of these problems during the pandemic. Method The analysis included N = 129 mothers (M = 39.98 years) and their children (M = 5.19 years). Via an online survey, which was held at different points during the pandemic, information on the children’s emotional problems was retrieved. The survey used the Strengths and Difficulties Questionnaire (SDQ). Data regarding the quality of attachment was collected via the Strange Situations Test (SST). At this point the participating children were approximately about12 months old. Results The calculation of a mixed ANCOVA showed, that attachment quality had a significant influence on children's emotional problems (F(2, 121) = 4.01, p = .021). The interaction effect between time and child attachment reached significance (F(3.45, 208.42) = 3.58, p = .011). The calculation of an additional mixed ANCOVA showed, that the reported emotional problems of girls were higher than those of boys F(1, 118) = 4.56, p = .035). Conclusions Our study shows that there is an association between attachment security and emotional problems and the impact of the SARS-CoV-2 pandemic on the mental health of preschool children in Germany. The emotional problems of all children increased, especially the disorganized attached children had been reported as emotionally stressed in the first lockdown. The results indicate the need for preventive services (for children and parents) to promote and maintain stress coping skills in order to maintain children’s mental health in times of crisis.